Recent approaches on disaster management - Misra, Anish (Random Publications, 2011)
Disaster is defines as a crisis situation causing wide spread damage which far exceeds our ability to recover. Thus, by definition, there cannot be a perfect ideal system that prevents damage, because then it would not be a disaster. It has to suffocate our ability to recover. Only then it can be called as 'disaster'. Disasters are not totally discrete events. Their possibility of occurrence, time, place and severity of the strike can be resonably and in some cases accurately predicted by technological and scientific advances. It is expected that the book would serve the interests of the students as source of information for understanding and appreciating the finer aspects of disaster management.